High-performance 1.06-μm InGaAs/GaAs double-quantum-well semiconductor lasers with asymmetric heterostructure layers. (9th April 2019) - Qiao, Zhongliang; Li, Xiang; Wang, Hong; Li, Te; Gao, Xin; Qu, Yi; Bo, Baoxue; Liu, Chongyang
Abstract: High-performance 1.06- μ m InGaAs/GaAs double-quantum-well (DQW) asymmetric herero- structure semiconductor lasers have been designed, fabricated and characterized. The laser structure, grown by metal-organic chemical vapor deposition (MOCVD), mainly consists of compositionally graded p-Alx Ga1−x As upper cladding layers, a p-Alx Ga1−x As upper waveguide layer, a 1.06- μ m InGaAs/GaAs DQW active region, an un-doped In1−x Gax Asy P1−y lower waveguide layer, and compositionally graded n-doped In1−x Gax Asy P1−y lower cladding layers. Measurement results of the as-cleaved ridge waveguide (RWG) lasers with a contact ridge width of 25 μ m and different cavity lengths (900 to 2765 μ m) demonstrated state-of-the-art performances with a high internal quantum efficiency ( η i ) of ∼98.4% and a low internal optical loss ( α i ) of ∼1.01 cm −1 at 20 °C. The laser has demonstrated high characteristic temperatures of 245 K ( T 0 ) and 663 K ( T 1 ) from 20 to 50 °C, and the cavity length dependent behaviour of T 0 and T 1 has also been investigated from 20 to 80 °C. Furthermore, a low transparency current density ( J tr ) of 77 A/cm 2 /QW in this laser structure is obtained at 20 °C, which is among one of the lowest values reported so far for 1.06- μ m InGaAs/GaAs semiconductor lasers.